Atomistic simulations of the Fe K-edge EXAFS in FeF3 using molecular dynamics and reverse Monte Carlo methods. (17th August 2016) - Jonane, Inga; Timoshenko, Janis; Kuzmin, Alexei
Abstract: Atomistic simulations of the experimental Fe K -edge extended x-ray absorption fine structure (EXAFS) of rhombohedral (space group R 3 ¯ c ) FeF3 at T = 300 K were performed using classical molecular dynamics and reverse Monte Carlo (RMC) methods. The use of two complementary theoretical approaches allowed us to account accurately for thermal disorder effects in EXAFS and to validate the developed force-field model, which was constructed as a sum of two-body Buckingham-type (Fe–F and F–F), three-body harmonic (Fe–F–Fe) and Coulomb potentials. We found that the shape of the Fe K -edge EXAFS spectrum of FeF3 is a more sensitive probe for the determination of potential parameters than the values of structural parameters ( a, c, x (F)) available from diffraction studies. The best overall agreement between the experimental and theoretical EXAFS spectra calculated using ab initio multiple-scattering approach was obtained for the iron effective charge q (Fe) = 1.71. The RMC method coupled with the evolutionary algorithm was used for more elaborate analysis of the EXAFS data. The obtained results suggest that our force-field model slightly underestimates the amplitude of thermal vibrations of fluorine atoms in the direction perpendicular to the Fe–F bonds.